Mendorong Legalitas dan Keberlanjutan UMKM Desa Blimbing melalui Penerbitan Nomor Induk Berusaha (NIB) - Hakim, M.Lutvi; Fitriana, Annisa; Nisa’, Ihda Sholihatin; Khamidah, Imroatul; Deril, Aliqa; Siwi, Nova Anjar; Kamilah, Naila Wardah; Octaviana, Bella; Amanda, Ruly Juventio; Saifudin, Mochammad; Mustakhim, Ahmad; Riskya, Eka Septi; Masruroh, Luluk; Sari, Denysa Ratna; Purnama, Fajrin Wahyuni; Permatasari, Fatimah; Kumalasari, Dwi Ayu; Muzaki, Ahmad Fahrul; Ifriqia, Fartika (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service program aims to encourage the legality and sustainability of MSMEs in Blimbing Village through the issuance of Business Identification Numbers (NIB). Business legality is an important factor in the development of MSMEs because it can increase market access, make it easier to apply for financing, and provide legal certainty for business actors. Many MSMEs in Blimbing Village have not been officially registered and have difficulty obtaining business legality. Therefore, this activity is carried out by providing assistance to MSMEs in the NIB application process via the Online Single Submission (OSS) platform. Methods for implementing activities include socialization, training, and direct assistance to business actors. The results of this activity show that MSMEs in Blimbing Village increasingly understand the importance of business legality and have successfully applied for an NIB for their business. With the NIB, it is hoped that MSMEs can develop further, gain consumer trust and be competitive in the wider market.